Economic and geopolitical perspectives of the Commonwealth of Independent States and Eurasia - Karnaukhova, Oxana; Udovikina, Alexandra 1989-; Christiansen, Bryan 1960- (IGI Global, Disseminator of Knowledge, 2018)
"This book explores the importance and influence of the CIS and Eurasia in the 21st century. It explores the following topics: international business in the former Soviet Union and Eurasia, the Russian Federation, commonwealth of independent states (cis), economic integration and disintegration, and successor states"...
Keywords: Commonwealth of Independent States; Gemeinschaft Unabhängiger Staaten; Wirtschaft; Geopolitik; Former Soviet republics -- History -- 21st century; Former Soviet republics -- Economic conditions -- 21st century; Former Soviet republics -- Politics and government -- 21st century; Former Soviet republics -- Foreign relations; Eurasien; Fallstudiensammlung